PENENTUAN LAPISAN TERKONTAMINASI RESIDU PUPUK MENGGUNAKAN METODA KELISTRIKAN PADA LAHAN PERTANIAN CEPAT PANEN - Ladaya A. Rakhmawati; Eleonora Agustine; Dini Fitriani; Mia Uswatun Hasanah (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Excessive fertilizer on farmland can increase or decrease mineral elements in the soil. If there is a change in the structure, then the land is a suspected of having the potential to experience contamination that affects the soil fertility. Cropping pattern in a farm area village "X" uses excess fertilizer due to short planting period, so it needs to identify the level of soil fertility on the farmland. One method that could use is the electrical method of rock. This method uses the observable magnetic properties of the ground to figure the value of the soil conductivity. The results showed that farmland in Village "X" has diverse conductivity values but has the same pattern. But when compared with the original soil (not farmland), there are striking differences. In addition to using the electrical method of rock, also conducted the soil color matching using Munsell Color.Keywords: Contamination, Conductivity, Rock Electrical, Munsell Color